2006
DOI: 10.1038/sj.npp.1301044
|View full text |Cite
|
Sign up to set email alerts
|

Tardive Dyskinesia in Schizophrenia is Associated with Prolactin-Related Sexual Disturbances

Abstract: Tardive dyskinesia (TD) may occur in never-medicated patients with psychotic illness, indicating the existence of non-medication, possibly disease-related, causes. We tested the hypothesis that, independent of the antipsychotic-induced rise in prolactin, the incidence of TD would be associated with the incidence of prolactin-related sexual disturbances (PRSD), which would be suggestive of a common pathology involving multiple dopamine tracts. Simple, global measures of TD and PRSD (loss of libido, amenorrhea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
(38 reference statements)
3
27
0
1
Order By: Relevance
“…Both the CATIE and SOHO studies found that other DIMD were associated with TD [43, 45]: the CATIE study showed that patients with TD had more parkinsonism and/or akathisia [43] while the SOHO study found that baseline extrapyramidal symptoms predicted TD [45], confirming our 1988 findings in a prospective study of TD [4]. In addition to reporting that the incidence of TD was lower in patients taking atypical compared to classical antipsychotics after 6 months [46], the SOHO study showed that the incidence of TD was associated with the incidence of prolactin-related sexual disturbances, independent of drug-induced changes in prolactin concentrations [47, 48]. …”
Section: Dimd and Dimd-associated Psychiatric Symptoms In The Time Pesupporting
confidence: 79%
“…Both the CATIE and SOHO studies found that other DIMD were associated with TD [43, 45]: the CATIE study showed that patients with TD had more parkinsonism and/or akathisia [43] while the SOHO study found that baseline extrapyramidal symptoms predicted TD [45], confirming our 1988 findings in a prospective study of TD [4]. In addition to reporting that the incidence of TD was lower in patients taking atypical compared to classical antipsychotics after 6 months [46], the SOHO study showed that the incidence of TD was associated with the incidence of prolactin-related sexual disturbances, independent of drug-induced changes in prolactin concentrations [47, 48]. …”
Section: Dimd and Dimd-associated Psychiatric Symptoms In The Time Pesupporting
confidence: 79%
“…In contrast, the Dutch treatment guideline classifies switching as level-3 evidence. 13 This guideline is based on 2 studies 23,24 with the strongest evidence coming from the industry-sponsored trial. 24 Our analysis, however, showed the opposite pattern, with a 3-point reduction on the AIMS for starting or switching to an FGA and a 2-to 3-point reduction for adding an SGA to FGA treatment.…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
“…[2][3][4] Movement disorders are especially prevalent among patients with serious mental illness (SMI), owing to frequent polypharmacy and because more severe symptoms are associated with increased risk of movement disorders. [5][6][7][8] The 2 most prevalent movement disorders in this sample are parkinsonism and tardive dyskinesia (TD). 1,9,10 Current treatment guidelines vary for the management of tardive dyskinesia.…”
mentioning
confidence: 99%
“…Previous studies investigated whether PRL levels could be used as a reliable biomarker of antipsychotic response (Gelder and Kolakowska, 1979;Ohman and Axelsson, 1978;Siris et al, 1978), schizophrenia symptomatology (Cotes et al, 1978), or TD in schizophrenia subjects (Cohen et al, 1979;Csernansky et al, 1983Csernansky et al, , 1986Kirkpatrick et al, 1989;Pandey et al, 1977;Smith et al, 1977;Tamminga et al, 1977;Tenback et al, 2006b). Most of the findings support that antipsychotic drugs modulate PRL levels but PRL should not be used as indicator of treatment outcome or its side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results led to the overall idea that dopamine hypersensitivity may be a selective process in the nigrostriatal pathway, not occurring in all dopaminergic systems. A more recent study associated TD with PRL-related sexual disturbances, suggesting an underlying common and central vulnerability that could be intrinsic to schizophrenia itself, and only detectable in the absence of external agents causing substantial increases in plasma PRL (Tenback et al, 2006b).In parallel with the clinical and biochemical measures, the search for TD predictors met the genetics field in early 1980s (Weinhold et al, 1981;Yassa and Ananth, 1981). The first studies evaluating first-degree relatives documented evidences of a genetic susceptibility component to develop TD (Delisi et al, 1982;Muller et al, 2001;Weinhold et al, 1981;Yassa and Ananth, 1981).…”
Section: Introductionmentioning
confidence: 99%